Strengthening Technology, Performance And Competitivness Of Apple Carang Mas “Arum Sari” In Batu City - Siti Asmaul Mustaniroh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACT Batu City is wellknown as apple icon as apple and aplle based products producer.